3D Printed Shape Memory Polymers Produced via Direct Pellet Extrusion - Trenton Cersoli; Alexis Cresanto; Callan Herberger; Eric MacDonald; Pedro Cortes (Micromachines, 2021)
Shape memory polymers (SMPs) are materials capable of changing their structural configuration from a fixed shape to a temporary shape, and vice versa when subjected to a thermal stimulus. The present work has investigated the 3D printing process of a shape memory polymer (SMP)-based polyurethane using a material extrusion technology. Here, SMP pellets were fed into a printing unit, and actuating coupons were manufactured. In contrast to the conventional film-casting manufacturing processes of SMPs, the use of 3D printing allows the production of complex parts for smart electronics and morphing structures. In the present work, the memory performance of the actuating structure was investigated, and their fundamental recovery and mechanical properties were characterized. The preliminary results show that the assembled structures were able to recover their original conformation following a thermal input. The printed parts were also stamped with a QR code on the surface to include an unclonable pattern for addressing counterfeit features. The stamped coupons were subjected to a deformation-recovery shape process, and it was observed that the QR code was recognized after the parts returned to their original shape. The combination of shape memory effect with authentication features allows for a new dimension of counterfeit thwarting. The 3D-printed SMP parts in this work were also combined with shape memory alloys to create a smart actuator to act as a two-way switch to control data collection of a microcontroller.